Saša Jazbec: Man taucht in eine andere Welt ein … Lesestrategien beim Lesen fremdsprachiger Literatur: eine empirische Studie am Beispiel slowenischer Germanistikstudentinnen und -studenten: (Siegener Schriften zur Kanonforschung, Bd. 9). Frankfurt am Main [etc.]: P. Lang, 2009. 258 str. - Kos, Dejan (Slavia Centralis, 2020)
The author presents the ninth volume of the collection Discussions on the Canon, published at the University of Siegen, in which Saša Jazbec discusses the starting points, potentials and perspectives of literary socialization and literary communication in a foreign language.
Keywords: Discussions on the Canon; Razprave o kanonu; literary socialization; literary communication; Man taucht in eine andere Welt ein; Saša Jazbec